Survival Differences in High-Risk Prostate Cancer by Age - García Fuentes, Clara; Guijarro, Ana; Hernández, Virginia; Gonzalo , Álvaro; Jiménez, Estíbaliz; de la Peña, Enrique; Pérez, Elia; Pérez, Elia; Llorente, Carlos (Urology Journal, 2023)
Purpose: Age is an established determining factor in survival in low-risk prostate cancer (PC), being this evidence weaker in high-risk tumors. Our aim is to evaluate the survival of patients with high-risk PC treated with curative intent and to identify differences across ages at diagnosis. Methods: We did a retrospective analysis of patients with high-risk PC treated with surgery (RP) or radiotherapy (RDT) excluding N+ patients. We divided patients by age groups: < 60, 60-70, and > 70 years. We performed a comparative survival analysis. A multivariate analysis adjusted for clinically relevant variables and initial treatment received was performed. Results: Of a total of 2383 patients, 378 met the selection criteria with a median follow-up of 8.9 years: 38 (10.1%) < 60 years, 175 (46.3%) between 60-70 years, and 165 (43.6%) >70 years. Initial treatment with surgery was predominant in the younger group (RP:63.2%, RDT:36.8%), and with radiotherapy in the older group (RP:17%, RDT:83%) (p = 0.001). In the survival analysis, significant differences were observed in overall survival, with better results for the younger group. However, these results were reversed in biochemical recurrence-free survival, with patients < 60 years presenting a higher rate of biochemical recurrence at 10 years. In the multivariate analysis, age behaved as an independent risk variable only for overall survival, with a HR of 2.8 in the group >70 years (95%CI: 1.22-6.5; p = 0.015). Conclusion: In our series, age appeared to be an independent prognostic factor for overall survival, with no differences in the rest of the survival rates.